Impact of Technology on HR in MSME - Yogashree V (Leading the Charge: A Guide to Management, Entrepreneurship and Technology in the Dynamic Business Landscape Edition 1, 2025)
Human Resources (HR) is very important in any organisation irrespective of sector. The term HR is used because it recognises people as a crucial asset, akin to equipment or supplies, essential for businesses to fulfil their objectives. Among all the resources at their disposal, employees are typically regarded as the most invaluable. Technology is significantly shaping various aspects of modern life, and it has increased the use of tools for HR management. From recruitment to talent management, compliance, payroll, and performance management, basic HR functions are undergoing transformation thanks to technology. Furthermore, emerging technologies are expanding HR’s role, focusing more on employee engagement and productivity. This study examines the impact of technology on Human Resources (HR) practices within the Micro, Small, and Medium Enterprises (MSMEs) sector. With the advent of digitalization, MSMEs are increasingly integrating technological solutions into their HR functions to streamline processes, enhance productivity, and improve employee engagement. A descriptive study is conducted on only the secondary data. This paper explores the various ways in which technology, such as HRIS (Human Resource Information Systems), AI (Artificial Intelligence), and data analytics, is reshaping recruitment, training, learning and development, performance management, and employee relations within MSMEs. Additionally, it investigates the challenges and opportunities associated with the adoption of technology in HR practices for MSMEs, considering factors such as cost, skill gaps, and organizational culture. The study highlights the transformative impact of technology on HR practices within MSMEs in Bengaluru.